2020
DOI: 10.3390/s20247073
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability of the Microsoft Kinect for Measuring Trunk Compensation during Reaching

Abstract: Compensatory movements at the trunk are commonly utilized during reaching by persons with motor impairments due to neurological injury such as stroke. Recent low-cost motion sensors may be able to measure trunk compensation, but their validity and reliability for this application are unknown. The purpose of this study was to compare the first (K1) and second (K2) generations of the Microsoft Kinect to a video motion capture system (VMC) for measuring trunk compensation during reaching. Healthy participants (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…[12] In addition, several studies have found Kinect V2 to be more valid and reliable for measuring ROM. [5,13] Studies on healthy subjects and patients with shoulder disorders or upper limb motor disorder in all ages will be included.…”
Section: Inclusion and Exclusion Criteria For Study Selectionmentioning
confidence: 99%
“…[12] In addition, several studies have found Kinect V2 to be more valid and reliable for measuring ROM. [5,13] Studies on healthy subjects and patients with shoulder disorders or upper limb motor disorder in all ages will be included.…”
Section: Inclusion and Exclusion Criteria For Study Selectionmentioning
confidence: 99%
“…Тогда можно прибегнуть к системе анализа движений тела, которая использует камеру и обычный ноутбук, анализирующий поступающие данные. Например, система Kinect разработана на базе интерфейса видеоигры и по результатам исследований признана эффективной в реабилитации пациентов с двигательными нарушениями [23]. Бюджетным вариантом также можно считать использование интерфейса «мозг-компьютер».…”
Section: современные перспективные методы физической реабилитацииunclassified
“…The Kinect could extract the temporal and spatial parameters of human gait, which does not need to accurately represent the human bones and limb segments, which solves the problem of event monitoring, such as the old people fall risk (Dubois and Bresciani, 2018). Based on a virtual triangulation method, an evaluation system for shoulder motion of patients based on the Kinect V2 sensors is designed, which can solve the solution of a single shoulder joint motion range of patients at one time (Cai et al, 2019;Çubukçu et al, 2020;Foreman and Engsberg, 2020). However, how to improve the efficiency of a multi-joint range of motion measurement combined with the teaching traction training method of the rehabilitation physician, how to use a single camera to accurately solve the problem of multi-joints spatial motion evaluation of human lower limbs, and how to avoid camera occlusion in the operation process of the rehabilitation physicians are an important basis for accurate input of lower limb motion information of rehabilitation robot.…”
Section: Introductionmentioning
confidence: 99%